Institutions, Performance, and the Financing of Infrastructure Services in the Caribbean. - Jha, Abhas Kumar, 1966- (World Bank working paper, 2005)
This book reviews the access to services, investment needs, tariffs, and efficiency of fifteen Caribbean countries across five infrastructure sectors (telecommunications, electricity, water and sanitation, maritime transport and ports, and airports and air services). Benchmarks are established to compare Caribbean countries with each other, and with similar countries. To some extent, differences in performance can be explained by unalterable factors such as a given country's size and location. However, we find that, in many cases, differences in performance among countries cannot be completely.